EU national parliaments and the recognition of palestine: “really” breaking new ground or “just” adding further support? (Comillas Journal of International Relations, 2016)
The European Union´s diplomacy has always given great importance and attention to the Israeli-Palestinian conflict. One key element in it is the question of the recognition of a Palestinian state. This article analyses this particular issue now that Sweden has recognized such a state, but it does so not only by looking at EU institutions and states: it also covers the reactions of three national parliaments: those of Spain, Italy and Greece. Thus, adding both to the literature on EU diplomacy and to that of parliamentary diplomacy, which is an emerging academic area of research.
Keywords: EU diplomacy; Israeli-Palestinian conflict; Palestine recognition; parliamentary diplomacy; Spanish Parliament; Italian Parliament; Greek Parliament